ALONE TOGETHER MENURUT SHERRY TURKLE DAN RELEVANSINYA BAGI KEHIDUPAN GEREJA DAN MASYARAKAT - Jamlean, Anselmus; Puah, Engelina (Pineleng Theological Review, 2024)
The essay discussed the phenomena of “alone together” in contemporary society. The idea “alone together” was developed by Sherry Turkle in the context of society where the communication technology plays a very pivotal role. The phenomena explains a tendency of modern people who are deeply connected in virtual world, but they are really alienated or alone in the real world. They focus more on virtual relationship, but neglect a personal relationship. Alone together also refers to a social reality where people feel more together when they enter the virtual world. Turkle wrote about the psychological symptoms of humans that draw them into connected social networks. The psychological symptoms are, feeling a sense of togetherness, expressing oneself according to one's wishes, freedom to express one's thoughts and feelings, and being able to express something difficult more easily without meeting.